2000
DOI: 10.1007/s002940000133
|View full text |Cite
|
Sign up to set email alerts
|

MSI1 suppresses hyperactive RAS via the cAMP-dependent protein kinase and independently of chromatin assembly factor-1

Abstract: RAS hyperactivation in the yeast Saccharomyces cerevisiae leads to multiple nutritional growth defects associated with overstimulation of the cAMP signaling pathway. Hyperactive RAS can be suppressed by overexpression of MSI1, a subunit of chromatin assembly factor-1 (yCAF-1). MSI1 overexpression suppresses phenotypes induced by increased cAMP content in multiple genetic backgrounds. However, MSI1 does not inhibit cAMP synthesis or total cellular cAMP-dependent protein kinase (PKA) activity, nor does MSI1 stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…1) in a CAF-I independent manner (Fig. 2), a result consistent with a recent report (51). Because CAC3 acts antagonistically with the Sin3p-Rpd3p complex (42) and the mammalian Cac3p homolog (RbAp48) is associated with chromatin-modifying enzymes such as histone deacetylases and histone acetylases (43,49), we asked if the CAC3 suppression of RAS2 G19V required histone-modifying activities such as the G19V -induced heat shock sensitivity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1) in a CAF-I independent manner (Fig. 2), a result consistent with a recent report (51). Because CAC3 acts antagonistically with the Sin3p-Rpd3p complex (42) and the mammalian Cac3p homolog (RbAp48) is associated with chromatin-modifying enzymes such as histone deacetylases and histone acetylases (43,49), we asked if the CAC3 suppression of RAS2 G19V required histone-modifying activities such as the G19V -induced heat shock sensitivity.…”
Section: Discussionsupporting
confidence: 87%
“…However, CAC3 overexpression did not affect the total level of extractable PKA kinase activity. Their data indicated that CAC3 suppressed the RAS/cAMP pathway in a CAC1-independent and BCY1-dependent fashion which is not fully understood (51). The results presented here support and extend their conclusions by indicating that Npr1p is the target of Cac3p that modulates the RAS/cAMP signal transduction pathway.…”
Section: Discussionmentioning
confidence: 45%
“…This Ccr4p-Not complex may mediate the repression of Msn2p and Msn4p by the PKA pathway. The PKA pathway may also alter chromatin structure (184). Finally, the PKA pathway has recently been shown to be a direct activator of pyruvate kinase (Cdc19p) (126) and Cox6p (176) in proliferating cells, suggesting a possible role for the pathway in regulating carbohydrate metabolism and mitochondrial function at the diauxic shift.…”
Section: Protein Kinase a Pathwaymentioning
confidence: 99%
“…The Ras/cAMP/PKA pathway has also been implicated in aging (212,216), thermotolerance (439), bud site selection, actin repolarization (333), glycogen accumulation (342), stress resistance (39,407), and sporulation (39,41); it may also regulate pseudohyphal differentiation (growth as chain-like multicellular filaments) in response to nutrient limitation. Each of these interesting topics (see reference 411 for a recent review), as well as the involvement in these processes of other nutrientstimulated kinases (e.g., Snf1 and TOR [45,75,196,197,401,441]), GTPases (e.g., Gpa2 [277]), and transcription factors (e.g., Msn2/Msn4 [30,96,112]), is outside the scope of this review.…”
Section: Early Steps In Signal Transductionmentioning
confidence: 99%